The representation|presentation of architecture in an exhibition: the portuguese example - Gomes, L. (Journal of Engineering and Architecture, 2019)
This article intends to approach the expositive phenomenon in the field of Architecture in Portugal, from a chronologically extended perspective, from its most consistent beginnings to contemporaneity. This approach allows a continuous image of the phenomenon, making possible the identification of patterns and the evolution of the options, the locations, the frequency and the themes recorded in their realization, and thus understand the evolution of the types of representations used, situate and understand the characteristics of the use of the various elements of representation | presentation, and in particular of the models in the Architecture exhibitions held in Portugal.